PREDICTORS OF ARTERIAL HYPO- AND HYPERTENSION BY SCHOOLCHILDREN - Евгений Васильевич Скударнов; Юрий Федорович Лобанов; Людмила Анатольевна Строзенко; Ольга Михайловна Малюга; Николай Алексеевич Дорохов; Виктор Сергеевич Пономарев (The Publishing House Medicine and Enlightenment, 2024)
Arterial hypo- and hypertension take one of the leading positions among cardiac pathologies by children of senior school age. The study purpose is to analyze the results of an objective examination of high school students and genealogical medical history data to identify predictors for the development of arterial hypo- and hypertension and to determine preventive measures for the health of adolescents. Materials and methods. There were analyzed data from a survey and objective examination of 75 graduate school teenagers in the city of Barnaul. In the general group of examined children females were more than males (42 girls and 33 boys, respectively). Statistical data processing was carried out using the Statistica 6 program. Results. The study made it possible to establish that in the general group of the study females dominated - 56 %. The presence of increased or decreased blood pressure was established by 26.7 % of adolescents, including 21.4 % of pubescent girls who had a decrease in blood pressure. Risk factors for arterial hypo- and hypertension include: a family history of arterial hypertension by 41.3 % of the examined children, overweight by 29 % of adolescents, sleep and rest disorders were found by 22 % of examined adolescents. Conclusion. The study of adolescents revealed the presence of changes in blood pressure. Elder children have a high percentage of hereditary history of arterial hypertension. Arterial hypo- and hypertension were significantly more often detected by adolescents during puberty with a family history of hypertension and overweight.